Molecular dynamics investigation of the ionic liquid/enzyme interface: Application to engineering enzyme surface charge - Burney, Patrick R.; Nordwald, Erik M.; Hickman, Katie; Kaar, Joel L.; Pfaendtner, Jim (Proteins, structure, function, and bioinformatics, 2015)
ABSTRACT Molecular simulations of the enzymes Candida rugosa lipase and Bos taurus α‐chymotrypsin in aqueous ionic liquids 1‐butyl‐3‐methylimidazolium chloride and 1‐ethyl‐3‐methylimidazolium ethyl sulfate were used to study the change in enzyme–solvent interactions induced by modification of the enzyme surface charge. The enzymes were altered by randomly mutating lysine surface residues to glutamate, effectively decreasing the net surface charge by two for each mutation. These mutations resemble succinylation of the enzyme by chemical modification, which has been shown to enhance the stability of both enzymes in ILs. After establishing that the enzymes were stable on the simulated time scales, we focused the analysis on the organization of the ionic liquid substituents about the enzyme surface. Calculated solvent charge densities show that for both enzymes and in both solvents that changing positively charged residues to negative charge does indeed increase the charge density of the solvent near the enzyme surface. The radial distribution of IL constituents with respect to the enzyme reveals decreased interactions with the anion are prevalent in the modified systems when compared to the wild type, which is largely accompanied by an increase in cation contact. Additionally, the radial dependence of the charge density and ion distribution indicates that the effect of altering enzyme charge is confined to short range (≤1 nm) ordering of the IL. Ultimately, these results, which are consistent with that from prior experiments, provide molecular insight into the effect of enzyme surface charge on enzyme stability in ILs. Proteins 2015; 83:670–680. © 2015 Wiley Periodicals, Inc.